Literature Review: Pesticide Residues on Vegetables in Indonesia - Rhamadini, Dhea; Meutia, Fayza; Husna, Yusfida Mariatul; Shafira, Nafka; Firdus, Firdus; Nasir, Muhammad; Rizki, Alia (International Journal of Health Sciences, 2024)
Pesticides are often used to control pests and improve the quality of agricultural products such as vegetables. However, excessive use of pesticides can leave residues on vegetables, which can harm the environment and human health. In addition, the Indonesian government's ban on using harmful pesticides on vegetables and the health risks associated with eating pesticide-contaminated food. Then strategies to manage pesticide residues, such as the use of organic fertilizers as pesticide substitutes, standardization of maximum limits of pesticide residues, monitoring pesticide residues, encouraging the use of pesticides separately, and training farmers. The conclusion in pesticide residues on vegetables is how important it is to manage pesticide residues on vegetables to maintain public safety and health.